Peran Advokat dalam Menangani Kasus Perlindungan Konsumen dalam Pengajuan Asuransi yang Mengandung Unsur Penipuan - Ira Sarawaty Sirait; July Esther (Bulletin of Community Engagement, 2024)
Consumer protection is a basic right that must be guaranteed by the state, especially in the insurance sector which has a high potential risk for consumers. Although Law No. 8 Year 1999 on Consumer Protection (UUPK) has provided a legal basis, there are still various challenges in its implementation, especially related to fraudulent practices that often occur in the process of filing insurance claims. This fraud can cause significant financial losses for consumers, both financially and psychologically. In this context, advocates have a very important role in protecting consumer rights, from assisting during the dispute resolution process to advocating for policy changes that better protect consumers. This research uses a normative juridical method with a literature study approach to analyze the role of advocates in handling cases of insurance fraud. It is hoped that the results of this study can provide a comprehensive understanding of the importance of the role of advocates as companions and protectors of consumer rights in the face of fraudulent practices of insurance companies and encourage the creation of a more fair, transparent and accountable insurance system